DIGITAL CLOCK USING AT89C5 - K.Geeth Vimal Kumar, G.Shruthi, N. Uma Sundari3, G.Vivek, P.Manivara Kumar (International Journal of Research Science and Management, 2016)
In this Project, a Digital clock is designed where the microcontroller is used for timing controller and the programming is also done in the microcontroller. The design is cost effective, simple and easy for maintenance. A clock is an instrument for measuring time. In principle it requires no more than some physical process which will proceed at a known rate, and a way to gauge how long that process has been continuing. Digital clocks display a numeric representation of time. Two numeric display formats are commonly used on digital clocks. They are: 24-hour notation with hours ranging 00 to 23 and 12 hour notation with AM/PM indicator. Most digital clocks use an LCD or LED display.Generally for the designing a digital clock, a microcontroller is used as the controller of the circuit and a Real Time Clock IC is used as counter. Our approach is to simulate the clock circuitry in Proteus 8.1 software with all the necessary interfacing connection and program. After simulating in the Proteus, we move to hardware implementation of the Digital clock.